Etnografski muzej - prostor praznovanja ranljivih skupin - Čeplak Mencin, Ralf (Etnolog. Nova vrsta (Ljubljana), 2013)
The article addresses (ethnographic) museums, which in the past thirty years have reorganised themselves and turned into institutions opening their premises to a variety of publics and social and political problems. These changes have been influenced by critical analyses of society, activists for human rights, the worsening financial crisis, democratisation, and numerous competing media and institutions. Festivals are an alternative form of museum activities. They are an attractive way of communicating with the public at different levels, while enabling disadvantaged creative people to play an active part in planning and realising various museum events, which can take place simultaneously at different locations.
Keywords: ethnology; etnologija; muzeji; muzejske zbirke; prireditve; festivali; Romi